Learning from magnetotactic bacteria: mms6 protects stem cells from oxidative damage - Wei, Nai-Li; Xu, Wenjing; Tang, Hai-Liang; Xie, Qiang; Zhai, Yuting; Chen, Jian; Zhang, Xiao-Yong; Zhu, Jian-Hong (Frontiers in Cellular Neuroscience, 2022)
Oxidative damage generally exists in stroke and impairs stem cells’ survival; however, the problem is difficult to treat. In order to help stem cells to resist this damage, we inserted a magnetotactic bacteria (MB) gene, mms6, into the neural stem cell genome by lentiviral transfection. It was found that the transfection of mms6 significantly improved the survival rate of stem cells in the condition of iron overload but not hypoxia, although their reactive oxygen species (ROS) levels decreased in both states. The bioenergetic profile also revealed that iron overloading weakened the mitochondrial respiration and spare respiration capacity of stem cells, but that these were enhanced after the expression of mms6. Additionally, Western blotting (WB) data revealed that mms6 upregulated the expression of glutathione peroxidase (GPX4), which protected stem cells from oxidative damage and ferroptosis. In order to determine the possible mechanisms, we analyzed the interactions between the MMS6 protein, Fe2+, and GPX4 via analog computation. The predicted models found that the MMS6 protein had a direct chelating site in the region of M6A with divalent iron; it also had weak binding with GPX4. Taken together, the magnetotactic bacterial gene mms6 protected stem cells from oxidative damage via binding with Fe2+, which could help them adapt to the microenvironment of stroke.